Application Of High-Strength Concrete To Drilled Shafts - 1. Summary - A. E. Fiorato (Deep Foundations Institute, 1991)
A test program was conducted to evaluate use of high-strength concrete in drilled shafts (caissons). The objective of the program was to determine if internal temperatures developed during cement hydration, or other characteristics of high-strength mixes, affect in-situ strength and stiffness. This paper covers strength results. Two 10-ft (3.0-m) diameter by 40-ft (12.2-m) deep caissons were constructed using two different commercially available high-strength concretes, a "low-heat" and a "high-strength" mix. Measured 6x12-in. (150x300mm) moist cured cylinder strengths at 56 days were 13,690 psi (94 MPa) for the "low-heat" mix and 17,130 psi (118 MPa) for the "high-strength" mix. Compressive strengths and moduli of elasticity of cores taken from the caissons were compared to those of companion cylinders made during casting of the caissons and stored in a moist room. Strengths of 4x8-in. (100x200 mm) cores taken at four ages and tested between 34 and 398 days averaged 81% of strengths of 6x12-in. (150x300 mm) moist cured cylinders at corresponding ages. In-situ (core) strengths of the caissons did not appear to be measurably affected by temperature. However, the data indicate that core strengths were sensitive to level of consolidation, as reflected in entrapped air voids. Overall, the results indicate that high-strength concretes can be used in drilled shaft (caisson) foundations.